Changes in Inequality of Family Income in Seven Industrialized Countries Responses to Growing Earnings Inequality - Peter Gottschalk (Luxembourg Income Study (LIS), 1992)
Discusses the distribution of family income, comparing the differing patterns of inequality measured only on income of heads and measured on total family income.
Keywords: 330